KEGIATAN ANALISIS JABATAN DI PT. BOSWA BERLIN MOTOR MAKASSAR - Ramadhani, Indri; Tetteng, Basti; Saputri, Sri Dewi; Rahmah, Tri; Mangarengi, Yusyah Alreffyanny; Cahyani, Indah (Devote: Jurnal Pengabdian Masyarakat Global, 2022)
PT Bosowa Berlian Motor Makassar is a company engaged in the sale of automotive goods and services. Within the company, it is necessary to carry out a job analysis to increase employee productivity through improvements and updates regarding existing job descriptions and job specifications. Data collection was carried out using interview. The data analysis used was a descriptive method, where the analysis was carried out by compiling job descriptions and job specifications at PT Bosowa Berlian Motor and providing recommendations for improvements to the positions that have been analyzed. In this activity, job analysis was carried out for 10 job holders, namely customer service sales, admin after-sales service, mechanics, customer satisfaction after-sales service, accounting staff, cashiers, spare parts sales, service advisors, and sales force.